The impact of omega-3 fatty acids, vitamins, minerals, N-acetylcysteine, and ginkgo biloba on the course and treatment of schizophrenia: A review of research and therapeutic perspectives - Niczyporuk, Patrycja; Zajkowska, Izabela; Giba, Aleksandra; Iłendo, Kamila; Królikiewicz, Wiktor; Marecki, Rafał; Kicman, Aleksandra (Quality in Sport, 2025)
Schizophrenia is a mental disorder with a complex etiology involving both genetic and environmental factors. Despite advancements in antipsychotic treatments, many patients continue to experience chronic symptoms and medication side effects. As a result, there is growing interest in dietary supplements and bioactive substances to complement traditional therapies and improve patient quality of life. Omega-3 fatty acids, vitamins, minerals, N-acetylcysteine, and ginkgo biloba have shown potential in supporting schizophrenia treatment. These substances may help regulate neuroinflammation, neurotransmission disturbances, oxidative stress, and improve cognitive function. This review examines the scientific evidence on their effects and explores the mechanisms behind their potential benefits in schizophrenia management.